PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA (STUDI KASUS PADA PERUM JAMKRINDO CABANG PEKANBARU) Vol. VIII. No. 3 Sep 2016 JURNAL TEPAK MANAJEMEN BISNIS1 PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA (STUDI KASUS PADA PERUM JAMKRINDO CABANG PEKANBARU) - Hasriani, Melly; Sasmita, Jumiati; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2016)
This research held in Perum Jamkrindo Pekanbaru in order to analyze eitherdirect or indirect influence of competency and organizational culture towards employeesâjob performance through work motivation. Research data consists of both primary andsecondary data which was collected by using questioner, documentary and interviews. Byusing census sampling, the respondents consists of 73 permanent employees of PerumJamkrindo Pekanbaru branch. Competency and organizational culture are used asexogeneous variable, while employeesâ motivation and job performance used asendogeneous variable. Data analyzed by using descriptive and path analysis which isassisted by SPSS 17 for windows. Result of this study shows that either competency andorganization culture directly effects to job performance. Employeesâ motivation itself has apositive and significant effect to job performance. Indirectly, work motivation can enhancethe effect of competency and organization culture to job performance. It is recommendedto enhance employeesâ job performance by increasing employeesâ competency,strengthening the implementation of organizational culture along with enhancing the workmotivation.